2011
DOI: 10.2478/v10181-011-0018-7
|View full text |Cite
|
Sign up to set email alerts
|

Cellular immune response of pigeons in the conditions of endotoxin fever and pyrogenic tolerance

Abstract: The aim of this study was to investigate changes in selected parameters of cellular immune response in the conditions of endotoxin fever and pyrogenic tolerance in pigeons. On the first day of observation the experimental birds (n=18) were intravenously injected with Escherichia coli LPS at a dose of 10 μg/kg b.w., while the control animals (n=6) received apyrogenic physiological saline also in the form of injection. On the second and the third day of the experiment LPS was injected additionally at 24 h interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Blood was sampled directly to K 2 EDTA-coated tubes and spleens were taken during the anatomopathological examination. Blood samples were prepared in accordance with the procedure described by Dudek (2011); spleen leukocytes for cytometry were obtained in accordance with the procedure described by Stenzel et al (2008). The percentage of CD4 + and CD8 + cells were read out in a lymphocyte gate and the results were analysed with the System II software.…”
Section: Methodsmentioning
confidence: 99%
“…Blood was sampled directly to K 2 EDTA-coated tubes and spleens were taken during the anatomopathological examination. Blood samples were prepared in accordance with the procedure described by Dudek (2011); spleen leukocytes for cytometry were obtained in accordance with the procedure described by Stenzel et al (2008). The percentage of CD4 + and CD8 + cells were read out in a lymphocyte gate and the results were analysed with the System II software.…”
Section: Methodsmentioning
confidence: 99%
“…The heterophils in control birds were by far lower from the standard of heterophils in chickens (30.1%, [20]). It has been reported in pigeons that infection (consecutive injection with E. coli LPS) resulted in decreased number of heterophils (heteropenia) [22]. The latter authors further suggested that acute infection may increase migration of most heterophils from circulation into tissues resulting in decreased proportion of heterophils in the blood.…”
Section: Discussionmentioning
confidence: 99%
“…[21] suggested that the increased numbers of lymphocytes (lymphocytosis) can be an indicator of acute infection and internal stress in chickens. Concomitant with the latter authors, Dudek and Bednarek [22] reported that the consecutive injection with E. coli lipopolysaccharides (LPS) resulted in lymphocytosis in pigeons. In this study, the concentration of globulin was higher in the serum of control birds when compared especially with the birds fed AC-FCP.…”
Section: Discussionmentioning
confidence: 99%
“…The mice with endotoxin tolerance had increased numbers of Kupffer cells, neutrophils and an increase in phagocytosis of bacteria [ 170 ]. In pigeons, a reduction of leukocytes and eosinophils occurs together with an increase in lymphocytes [ 171 ]. Moreover, the endotoxin tolerance did not prevent the early TLRs signalling; nonetheless, it limited the later development of the inflammatory systemic disease.…”
Section: Ido1 Kp Activation and Innate Immunity In Sepsismentioning
confidence: 99%